CASSANDRA – a tool for analysis and prediction of time resolved BO defect dynamic on lifetime and cell level. (September 2017) - Herguth, Axel; Wilking, Svenja
Abstract: A numerical simulation tool – CASSANDRA – has been created which can simulate time resolved boron-oxygen related defect dynamic on lifetime and solar cell level. The model is based on the fundamental lifetime limitation due to BO defects and a set of linear differential rate equations. CASSANDRA includes not only BO defect related lifetime injection dependence, but also injection level feedback under non-constant injection (often constant generation) experimental conditions. This allows for analysis and prediction of experiments not only on lifetime level, but also on solar cell level as well. In a virtual experiment it is demonstrated how CASSANDRA reveals the otherwise hidden defect dynamic. Besides time resolved simulations, long term equilibrium situations may be simulated as well, e.g., performance in the degraded vs. non-degraded case.